The English House - Aslonova Malohat Fayzulloyevna (Zien Journals, 2022)
The English House is a book of design and architectural history written by German architect Hermann Muthesius and published in 1904.[1] Its three volumes provide a record of the revival of English domestic architecture during the latter part of the nineteenth century.[2] The main themes he discusses are history, form and decor.
Keywords: architectural; English; German; domestic